A one step processed advanced interwoven architecture of Ni(OH)2 and Cu nanosheets with ultrahigh supercapacitor performance. Issue 31 (15th July 2016) - Shi, D.; Zhang, L.; Yin, X.; Huang, T. J.; Gong, H.
Abstract : A facile and green one-step synthesis of an advanced interwoven architecture of Ni(OH)2 and Cu nanosheets with ultrahigh supercapacitor performance. Abstract : In this work, an interwoven nanoscale structure of Ni(OH)2 and copper is successfully grown on Ni foam (NF) by using a one-step cheap chemical method. The concurrently formed structure with active Ni(OH)2 growing together with the conductive Cu network facilitates fast electron transport throughout the electrode. As a result of enhanced conductivity by Cu and ultrathin nanosheet morphology of the active material, the Ni(OH)2 –Cu hybrid electrode delivers an ultrahigh areal capacitance (8.66 F cm −2 at 1 mA cm −2 ), superior rate capability (79.1% capacitance retention at 20 mA cm −2 and 61.8% capacitance retention at 50 mA cm −2 vs. 1 mA cm −2 ) and outstanding cycling stability (98.5% capacitance retention after being charged/discharged at a series of current densities for 3500 cycles). Furthermore, the full cell, with Ni(OH)2 –Cu/NF as the positive electrode and reduced graphene oxide (RGO) as the negative electrode, delivers high areal capacitances and superior energy densities especially at high rates. The involved mechanisms are analyzed and discussed.